Hierarchical 2H/1T-MoSe2@graphene on cotton fabric for multifunctional and flexible microwave absorption. (5th March 2023) - Zhang, Yunfei; Zhang, Lei; Zhou, Bingqian; Cheng, Haichuan; Zhang, Qiuyu; Zhang, Baoliang
Abstract: Molybdenum selenide (MoSe2 ), as a potential electromagnetic wave (EMW) absorber, its phase influence on the EMW absorption performance has not yet been investigated. Herein, we synthesized MoSe2 by a one-step hydrothermal approach, while controlling the intensity of reduction process to modulate the phase of MoSe2 . The influence of MoSe2 with different phases on the EMW absorption performance is intuitively revealed by comparing corresponding performances. Remarkably, 2H/1T-MoSe2 exhibit the optimal absorption performance with a minimum reflection loss (RLmin ) of −52.3 dB@16 GHz and an effective bandwidth (EAB) of 6.4 GHz at 2.1 nm thickness, which cover the whole Ku band. Besides, to meet the growing demand for wearable electronics, a flexible microwave absorbing material with RLmin of −33.4 dB@9.1 GHz was created by constructing 2H/1T-MoSe2 @RGO layered nanostructures on the surface of cotton fabric. Especially at the thickness of 3.3 mm, EAB can cover the whole X-band. Above composite fabrics also possess excellent self-cleaning and corrosion resistance as a result of layered nanostructures and hydrophobic coatings. This work not only provides a crucial reference for advancing the electromagnetic wave absorption performance via phase engineering, but also proposes an novel idea for the development of fiber-based multifunctional flexible microwave absorbing materials. Graphical abstract: Image 1 Highlights: MoSe2 with different phases are controllably prepared by phase engineering. The phase influence of MoSe2 on the EMW absorbing performance is first revealed. A self-cleaning and corrosion-resistant flexible microwave absorber is prepared. Electromagnetic parameters of composite fabric are adjusted by changing RGO loading.